Modern X86 assembly language programming : covers X86 64-Bit, AVX, AVX2, and AVX-512 - Kusswurm, Daniel (Apress, 2018)
Gain the fundamentals of x86 assembly language programming and focus on the updated aspects of the x86 instruction set that are most relevant to application software development. This book covers topics including the new Advanced Vector Extensions (AVX) 512 programming, from the latest x86 instructions set, and the MMX technology and instruction set. The focus in this second edition is exclusively on 64-bit base programming architecture and AVX programming. Modern X86 Assembly Language Programming's structure and sample code are designed to help you quickly understand x86 assembly language programming and the computational capabilities of the x86 platform. After reading and using this book, you'll be able to code performance-enhancing functions and algorithms using x86 64-bit assembly language and the AVX, AVX2 and AVX-512 instruction set extensions.